2014
DOI: 10.1007/s00405-014-3275-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observations and risk factors for tinnitus in a Sicilian cohort

Abstract: The aims of this study were to determine the distribution of risk factors associated with tinnitus analysing their role in the development of tinnitus and the effects of their interaction; to evidence the importance of a suitable and adequate clinical and audiologic assessment to avoid those modifiable risk factors responsible for cochlear dysfunction and tinnitus onset. 46 subjects with tinnitus and 74 controls were studied according to: age, sex, Body Mass Index (BMI), neck circumference, tobacco smoking, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 34 publications
9
38
2
4
Order By: Relevance
“…Many studies in adult populations reported that the tinnitus prevalence was higher in males or equal between the two sexes . However, most recent epidemiological studies on tinnitus in adults showed a similarity between genders or a small increase in women compared to men . Additionally, one report found that the prevalence in pediatric tinnitus was higher in females .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies in adult populations reported that the tinnitus prevalence was higher in males or equal between the two sexes . However, most recent epidemiological studies on tinnitus in adults showed a similarity between genders or a small increase in women compared to men . Additionally, one report found that the prevalence in pediatric tinnitus was higher in females .…”
Section: Discussionmentioning
confidence: 99%
“…Although smoking has been proposed as a potential risk factor for tinnitus in both adults and children, studies have failed to obtain consensus . However, many studies have revealed that smoking can influence the vital structures of the auditory tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acufenometry included pitch masking (matching the frequency of the tinnitus with a variety of stimuli) and loudness matching (estimating the loudness of tinnitus with a pure tone or noise); the difference between the hearing threshold and the sensation level was considered tinnitus loudness (0-5 dB, 5, 10, 15, [15 dB above the hearing threshold) [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…One study reported an association between nighttime blood pressure and tinnitus . In addition, stress, decreased sleep, hyperlipidemia, osteoarthritis, rheumatoid arthritis, asthma, diabetes, thyroid disease, hypertension, increased body mass index (BMI), increased neck circumference, anxiety, and depression have been shown to be associated with increased reported tinnitus …”
Section: Introductionmentioning
confidence: 99%